Analysis of the application of vibration diagnostics and thermography methods for an early detection of defects in an industrial mixer-gearbox system – a case study - Novaković, Borivoj; Djordjević, Luka; Jerković, Damir; Bakator, Mihalj (Vojnotehnički glasnik / Military Technical Courier, 2025)
Introduction/purpose:Bearings constitute essential components without which the functioning of systems subject to significant loads would be inconceivable. The bearing installation process in rotational systems diligently influences their longevity, reliability, and efficiency. Accurate and meticulous bearing installation is of paramount importance to ensure optimal operational performance of rotational systems. Proper bearing assembly assists in the even distribution of loads, reduction of friction, and minimization of wear. Additionally, appropriately mounted bearings decrease the risk of vibrations, noise, and potential system failures. Therefore, the bearing installation process represents a crucial step in maintaining the reliable and efficient operation of rotational systems, thereby extending their operational lifespan and reducing the need for repairs.Methods: The methodology employed in this study combines vibrodiagnostic analysis of an industrial mixer equipped with a planetary gearbox and the concurrent application of thermographic techniques. This integrated approach provides a comprehensive understanding of the system's condition and helps identify potential sources of heating within both the gearbox and the mixer. Vibrodiagnostic examinations encompassed the analysis of vibrations generated by the planetary gearbox during its operation, coupled with the interpretative scrutiny of results aimed at detecting possible imbalances, damages, or irregularities within the mechanical system. On the other hand, the application of thermography contributed to generating a visual representation of temperature distributions at critical points of the gearbox, facilitating the identification of thermal anomalies. The integration of these methods enables a holistic scientific approach to the analysis of the planetary gearbox system, allowing for detailed diagnostics and an understanding of the root causes of potential operational issues in the gearbox.Results:The meticulous interpretation of acquired data facilitated the identification of potential causes of thermal loading in the planetary gearbox, providing a comprehensive insight into the mechanical and thermal facets of the entire system. The integration of vibrodiagnostic and thermograpfic methods constitutes a pivotal component of a holistic analytical approach, crucial for an exhaustive understanding of the performance and overall condition of the planetary gearbox and industrial mixer. The obtained results serve as the foundation for the development of precise diagnostic procedures, laying the groundwork for the implementation of pertinent improvements or maintenance strategies within the system. This, in turn, holds the potential to optimize the operational performance of the planetary gearbox and extend its operational lifespan.Conclusion: The applied methodology, based on vibrodiagnostic analyses and thermographic techniques, has provided a comprehensive insight into the condition of both the planetary gearbox and the industrial mixer containing it, with all analyses described in the text conducted on each component within the mixer system. The detailed interpretation of data has enabled the identification of potential causes of gearbox heating, offering a deeper understanding of the mechanical and thermal aspects of the system. In this manner, the efficiency of maintaining the examined system can be enhanced.
Keywords: planetary gearbox; industrial mixer; vibrodiagnostic; thermograpfic; analysis; bearing; reliability; maintenance